PENERAPAN MEDIA KONKRET UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK INTEGRATIF PESERTA DIDIK KELAS 2 MINU NGINGAS - Salsabila, Zuha Prisma; Aliya, Nafisatul; Susanti, Fadillah Mira; Putri, Nurleila Rizqi; Indriyanti, Putri; Al Wafa, Achmad Syaab Arif; Chasanah, Uswatun (AULADUNA: Jurnal Pendidikan Dasar Islam, 2022)
Abstract This study aimed to improve students' learning outcomes in class 2 of MINU Ngingas Sidoarjo by using concrete media in integrative thematic learning. The method used was Classroom Action Research (CAR), including two cycles. Each cycle consisted of three stages: planning, action and observation, and reflection. Data collecting procedures used were test, observation, and interview techniques. The observations showed the problem of students' disinterest in lecture learning. Interview data gave the result that students did not understand abstract material. The problem found was no usage of real media, so it affected students' understanding. Actions using concrete media in integrative thematic learning indicated that applying concrete media to integrative thematic learning could improve students’ learning outcomes in class 2 of MINU Ngingas Sidoarjo. Concrete media was very influential in improving students’ learning outcomes in integrative thematic learning in class 2 of MINU Ngingas Sidoarjo.